Geography in the final years of elementary school: an analysis of public and private education in the municipality of Patos-PB - Sobrinho, Antonio Izidro (Revista Ensino de Geografia (Recife), 2020)
The knowledge related to Geography is very significant for the understanding of the current world, however, it is seen that that this knowledge has different treatments when analyzing their applicability in public and private schools. This article sought to identify the difficulties faced by Geography teachers in these two school systems regarding the transmission of geographical knowledge. In order to this, an exploratory research was carried out through the application of questionnaires in 10 educational institutions, 5 public and 5 privates. It was noticed that Geography teachers from public school face structural problems such as the lack of didactic resources and social problems such as the absence of the family in the school environment. In this regard, several authors such as Kaercher (2010) talk about a methodological change on the part of teachers, but it turns out that they have other challenges that present greater difficulties to be overcome. It is concluded, therefore, that the disparity between the public and private schools in elementary education in the municipality of Patos-PB is not due to the incapacity of teachers, but rather due to a scarcity of resources that help in the development of classes, making them more dynamic and attractive